ИННОВАЦИОННОЕ РАЗВИТИЕ ГОСТИНИЧНОГО БИЗНЕСА КАЗАХСТАНА (Journal of Economic Research & Business Administration, 2015)
The article considers perspectives of developing hotel business, highlighting hotel «Қazjol».